Optimizing Writing Skills through Problem-Based Learning and Scrablle Media in Elementary Schools - Siska, Siska; Mukmin, Mukmin; Hidayah, Nurul; Ambarwati, Niken Putri; Tillah, Mardha (Nurul Jadid University, 2025)
Maharah kitabah (writing skills) is an important component in Arabic language learning that requires an innovative approach. This study aims to analyze the effectiveness of using the Problem Based Learning (PBL) model and scrabble media in improving Arabic writing skills of students at SDIT Al Hidayah Palembang. This study uses a combination research method (mix method) with a sequential explanatory model, involving 23 fifth grade students who became the experimental class. The research instruments include observation, interviews, documentation, pre-test and post-test. The results showed that the application of PBL and scrabble media significantly improved Arabic writing skills, with an average increase in post-test scores reaching 85.87 compared to the average pre-test of only 65.00. The findings of the study revealed that the combination of the PBL model and scrabble media was effective in optimizing maharah kitabah, increasing active participation, learning motivation, and students' creativity in writing Arabic. This study provides theoretical and practical contributions to the development of innovative and interactive Arabic language learning strategies.